The Size Distribution of Manufacturing Plants and Development - Kothari, Siddharth (Washington, D.C. : International Monetary Fund, 2014)
The typical size distribution of manufacturing plants in developing countries has a thick left tail compared to developed countries. The same holds across Indian states, with richer states having a much smaller share of their manufacturing employment in small plants. In this paper, I explore the hypothesis that this income-size relation arises from the fact that low income countries and states have high demand for low quality products which can be produced efficiently in small plants. I provide evidence which is consistent with this hypothesis from both the consumer and producer side. In particular, I show empirically that richer households buy higher price goods while larger plants produce higher price products (and use higher price inputs). I develop a model which matches these cross-sectional facts. The model features non-homothetic preferences with respect to quality on the consumer side. On the producer side, high quality production has higher marginal costs and requires higher fixed costs. These two features imply that high quality producers are larger on average and charge higher prices. The model can explain about forty percent of the cross-state variation in the left tail of manufacturing plants in India.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet